2016
DOI: 10.1007/s10067-016-3515-3
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk assessment in patients with rheumatoid arthritis: a correlative study of noninvasive arterial health testing

Abstract: Objectives This study aimed to determine the relationship between noninvasive measures of arterial health and both estimated 10-year cardiovascular risk and measures of disease activity over time in established rheumatoid arthritis. Methods Fifty rheumatoid arthritis patients underwent noninvasive arterial health testing (brachial artery reactivity, aortic augmentation index pulse wave velocity [AIx], carotid artery intima-media thickness, and carotid artery plaque presence) and assessment of clinical diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…Temiz et al provided further evidence that EAT correlated with cIMT and FMD in RA patients and suggested that EAT could serve as a surrogate marker for estimating the extent of vascular involvement [36]. However, AS may represent a more accurate marker of disease burden over time than FMD, as recent evidence indicated [47].…”
Section: Discussionmentioning
confidence: 99%
“…Temiz et al provided further evidence that EAT correlated with cIMT and FMD in RA patients and suggested that EAT could serve as a surrogate marker for estimating the extent of vascular involvement [36]. However, AS may represent a more accurate marker of disease burden over time than FMD, as recent evidence indicated [47].…”
Section: Discussionmentioning
confidence: 99%
“…Вывод о взаимосвязи воспалительной активности при РА (DAS-28 с параметрами артериальной ригидности (СРПВ, ИА) получен и в работе Scanlon E. с соавт. [31]. Связь снижения эластических своиств сосудов (оценка на основании СРПВ) у больных РА с выраженностью и неконтролируемой активностью воспаления, а также с повышением АД продемонстрирована и в ряде отечественных работ [32,33].…”
Section: Discussionunclassified
“…Many imaging tools such as coronary artery calcification by multi-slice computed tomography [39], intima–media thickness by carotid ultrasound [40], arterial stiffness with aortic pulse wave velocity or arterial augmentation index, ankle–brachial index [4143], and echocardiography [44], have been proposed to measure subclinical vascular damage in RA. Among these, only carotid ultrasound has been included in EULAR recommendations for clinical practice, based on the evidence that carotid plaques in RA are associated with disease duration, disease activity, and ischemic heart disease with poor CVD-free survival [4547].…”
Section: Introductionmentioning
confidence: 99%